Use of Diagnostic Musculoskeletal Ultrasound in the Evaluation of Piriformis Syndrome: A Review for Rehabilitation Providers - Robert C. Manske; Chris Wolfe; Phil Page; Michael Voight; Beth Bardowski (International Journal of Sports Physical Therapy)
Piriformis Syndrome (PS) is a neuromuscular condition caused by the entrapment of the sciatic nerve at the level of the piriformis muscle (PM) and can cause significant discomfort and disability. PS is often misdiagnosed due to its overlapping symptoms with other lumbar and sciatic issues and as such, diagnosing PS remains challenging despite recent invasive and non-invasive diagnostic methods. Diagnostic musculoskeletal ultrasound (MSK US) offers a non-invasive, cost-effective alternative for the identification and evaluation of PS, providing dynamic, real-time imaging of the PM and adjacent structures. This article reviews the applications, advantages, and procedural insights of MSK US in the diagnosis of PS, emphasizing its relevance in rehabilitation settings. We discuss the technical aspects of ultrasound use, interpretation of findings, and integration into clinical practice, aiming to enhance the diagnostic accuracy and therapeutic outcomes for patients with suspected PS.